Penyakit Paru Interstisial pada Sindrom Sjogren Primer - Notariza, Kemas Rakhmat; Nurwidya, Fariz (Majalah Kedokteran Indonesia, 2024)
Interstitial lung disease (ILD) is the most common extraglandular manifestation in primary Sjogren’s syndrome (pSS), the second most prevalent autoimmune rheumatic disease. This literature review aimed to discuss about ILD in pSS (pSS-ILD), beginning from aspect of epidemiology, classification criteria, monitoring of disease activity, pathogenesis, diagnostic approaches, to management. The 2016 American College of Rheumatology (ACR)/European League Against Rheumatism (EULAR) classification criteria for pSS are useful for establishing a diagnosis of pSS. The level of disease activity can be assessed by using the EULAR Sjogren’s Syndrome Disease Activity Index (ESSDAI). Development of autoimmunity to epithelial cells is the pathogenesis mechanism of pSS not only in exocrine glands but also extraglandular, including the lungs. The main diagnostic modalities recommended in the screening and monitoring of ILD in pSS are pulmonary function tests (PFTs) and high-resolution computed tomography (HRCT) of thorax. Systemic therapy options for pSS-ILD include glucocorticoids, immunosuppressive agents and biological drugs.